MEDIA PEMBELAJARAN TEMATIK KURIKULUM 2013 BAGI GURU-GURU SD NEGERI 2 PALEMBANG - Marwan Pulungan; Nuraini Usman; Toybah Toybah; Siti Dewi Maharani; Vina Amilia Suganda (Universitas Sriwijaya, 2020)
Learning media is one of the supporters in the success of the learning process and student learning outcomes. Thematic learning in elementary schools in the 2013 curriculum, it is deemed necessary to be equipped with learning media in the learning process in the classroom. It is intended that teachers develop innovations in learning by being able to create and use learning media, so that problems in the classroom can be minimized. This training aims to provide understanding and motivate the teachers of SD Negeri 2 Palembang to be able to create and use thematic learning media in the 2013 curriculum to support the learning process in the classroom. This activity is a guided training. who came from SD Negeri 2 Palembang, amounting to 20 participants. Training on the creation and use of thematic learning media in the 2013 curriculum has a positive impact on knowledge and self-development for teachers of SD Negeri 2 Palembang. Key Words: media, thematic learning, 2013 curriculum